Meningkatkan Hasil Belajar Siswa pada Pelajaran PKn dengan Menggunakan Metode Role Playing di Kelas V SDM Karuni - Zangga, Yohanes Goalbertus; Ngongo, Khristoforus Palli; Daga, Agustinus Tanggu (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the improvement in student learning outcomes in Civic Education (PKn) through the application of the Role Playing method in the subject matter of cultural, social, and religious diversity and tolerance. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 26 fifth-grade students at SDM Karuni, consisting of 15 male students and 11 female students. Data collection techniques included observation of teacher and student activities, learning outcome tests, and documentation to support quantitative and qualitative data. Data analysis was conducted using quantitative descriptive analysis to calculate the increase in learning outcomes and qualitative analysis to describe changes in student behavior and learning activities during the action. The results of the study indicate that the application of the Role Playing method can significantly improve student learning outcomes. The average class score increased from 65.33 in cycle I to 80 in cycle II, with classical mastery increasing from 47% to 80%. Teacher activity also increased from 60.22 to 82.95, while student activity rose from 59.72 to 77.77. Thus, the application of the Role Playing method proved to be effective in improving student learning outcomes in Civics Education in Grade V at SDM Karuni.